Psychometric properties analysis of the Motivational Self-Regulation Strategies Questionnaire - Freiberg Hoffmann, Agustín (2025)
Motivational self-regulation allows students tosustain and/or improve their motivation to achieve their goals. Thisself-regulation variant is related to variables such as academic performance,classroom climate, and academic procrastination, among others. The MotivationalSelf-Regulation Strategies Questionnaire (MRSQ) operationalized the construct. Thequestionnaire was adapted in Córdoba (Argentina), dividing the dimensions ofgoal regulation according to the strategies employed — whether by approximationor avoidance. The present research proposes to analyze new evidence of thevalidity and reliability of the MRSQ. A total of 412 university students fromBuenos Aires (Argentina) participated in the study. The analysis of theinternal structure of the instrument using confirmatory factor analysis (CFA)and exploratory structural equation modeling (ESEM) verified a better fit forthe 8-factor model. Further, a measurement invariance analysis between samplesof students from Buenos Aires and Córdoba verified the metric equivalence ofthe MRSQ. The internal consistency of the dimensions was adequate (> .70).Next, the concurrent validity test yielded positive and significantcorrelations with learning approaches and negative correlations with academicprocrastination. Statistical norms were also computed. This work provides newevidence on the psychometric properties of the MRSQ and norms that enable itsuse and interpretation within applied settings.